The role of precipitation and soil moisture in enhancing mercury air-surface exchange at a background site in south-eastern Australia. (15th June 2021) - MacSween, Katrina; Edwards, Grant C.
Abstract: Soil moisture and precipitation are important parameters that influence Hg air-surface exchange at background sites, thereby influencing Hg distribution in the environment. Australia is a unique and understudied climatic region. Rainfall across the temperate regions of Australia is highly variable on both annual and inter-annual scales and is overall a relatively dry continent. As such, it is plausible that Australian terrestrial fluxes do not respond to precipitation and soil moisture changes in the same way as observed in the Northern Hemisphere. This study focused on investigating Hg flux in response to precipitation and soil moisture changes at a background site in south-eastern Australia over a 14-month measurement period. The Austral summer experienced the highest rainfall, with a cumulative average of 3.21 mm d −1 and rainfall occurring during 5.95% of the half-hourly measurements during this period. Autumn 2018 had the lowest daily rainfall (1.20 mm d −1 ). Hg fluxes during rainfall averaged 1.03 ng m −2 h −1 (standard deviation (SD), 20.78), compared to the overall study average of 0.002 ng m −2 h −1 (SD 14.23), signifying influence from the occurrence of rain. Mercury fluxes at this site show substantial spikes that often coincided with the occurrence of rainfall. Mercury released from the substrate during rainfall is primarily due to the interstitial release of Hg as the water infiltrates the soil pore space. Deposition during rainfall also indicated rapid recycling of Hg between the soil and air. There was little evidence of enhanced Hg fluxes occurring caused by increased soil volumetric water content. Lack of enhancement suggests that Hg stores within the substrate are depleted during the initial release. Highlights: Investigated Hg flux in response to precipitation at a background site in Australia. Hg fluxes during rainfall were higher than the overall study average. Hg fluxes showed spikes during rainfall due to interstitial release from the substrate. Little evidence of enhanced Hg fluxes occurring because of increased soil moisture. Lack of enhancement suggests Hg within the substrate is depleted during initial spike.